KESIAPAN BERSEKOLAH ANAK TAMAN KANAK-KANAK KELOMPOK B DITINJAU DARI LEMBAGA PENDIDIKAN DAN TINGKAT PENDIDIKAN ORANG TUA - Srinahyanti, Srinahyanti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This study is a comparative study that illustrates the difference between school readiness by kindergarten status Â and the level of parental education. This research is motivated by the importance of school readiness as the basis for children to learn and achieve achievement in elementary school. In addition, this study is also directed to see the readiness of children to enter elementary school from various aspects. Therefore, the purpose of this study consists of two,to provide information about the readiness of readiness and to know the difference of child readiness of different groups of differentiating variables. Approach and method used in this research is quantitative approach with non-experimental method of comparative with research sample of kindergarten children class B in Sukasari sub-district of Bandung city as many as 100 children. The school readiness measurement tool used in this study is Nijmeegse Schoolbekwaamheids Test (N.S.T.). The analysis of the data is done quantitatively by means of the mean, whitney u test and cruciate test of willis. From the results of N.S.T test shows that 76% of the sample of children declared mature and ready to enter further education (SD) but there are some aspects that need to be developed that is the ability of sharpness of observation and self-knowledge and limbs. While calculation of man whitney u and kruskal wilis show no difference of school readiness seen from kindergarten status, parent education level. This means that to see school readiness in children does not need to see the kindergarten status that the child follows, the level of education and income of the parents. Recommendations are addressed to Kindergarten educators, and other researchers looking to examine school readiness in children.Â Key Words: School Readiness, Kindergarten, Kindergarten Status, Level of Parent Education,